Innovative Food Quality Models – Developed as an Interface for Modern Consumers and Sustainable Business - Rodica Pamfilie; Magdalena Bobe; Lavinia Cristescu; Maria Alexandra Toma (Amfiteatru Economic Journal, 2016)
The intensive development of global markets correlated with the modern consumer's demands led to a new complex approach concerning the food sector and its' main determinants. Old market theories that describe the food market mechanisms as a simple three point process: "to produce – to sell – to buy" are now growing into elaborated models based on more determinants that have one common challenge: quality. Thus, the present study aims to highlight the importance of producers' accountability in ensuring the quality of food products, by implementing standardize methods of production and by informing the consumers in a correctly and completely manner. In other words, the research focuses on quality management systems as defining instruments that can assure high-quality food products are being delivered at competitive prices to domestic and international markets. In this sense, food quality management principles are analyzed from the point of view of one of the biggest actors in the food industry, Mondelez International. Having as a starting point the interview results with the Procurement Innovation Manager in Quality, this paper manages to outline a consumer preference based model in developing new food products. The present conceptual model takes into consideration both quality specialist and consumer's demands, in order to maintain the requirements of food management and safety systems and, simultaneously, to be flexible and optimize new food products according to modern consumer's quality requirements: design.
Keywords: L15; L66; Q55; M11; 330; quality management; food safety; consumer inspired design; sustainable business; innovative model; modern consumers' needs